Selçuklu Anadolusu'nda av ve avcılık (1075-1318) - Salman, Ahmet (My University, 2022)
Yazılan bu tez insanlık tarihinde mühim bir beslenme faaliyeti olan avcılığın Selçuklu Anadolusu’nda (1075-1318) uygulanmasını konu edinmektedir. Bilindiği üzere Anadolu Selçuklularının politik, diplomatik alanlarına dair çalışmalar yapılmasına karşın devleti ve o dönemki toplumu anlamada önemli bir konu olan avcılığa dair çalışmalarda eksiklikler vardır. Bu kapsamda dönemin vakayinameleri, edebî eserleri ve çağın sanatsal ürünleri incelendiğinde, Anadolu’da avcılığa dair zengin bir malzeme olduğu kanaatine varılmış; tez de bu doğrultuda şekillenmiştir.

This thesis is about hunting in Seljuk Anatolia, which is an important activity in the history of humanity (1075-1318). Although there is research on the Anatolian Seljuks political and diplomatic fields, there are deficiencies in the studies on hunting, which is an important aspect of understanding the state and society at the time. When the period's chronicles, literary works, and artistic objects of the time were analyzed in this context, it was concluded that Anatolia had a treasure of hunting material, and the thesis was shaped in this direction.
Keywords: Anadolu Selçukluları; Av; Avcılık; Doğan; Hawk; History; Hunting; Prey; Sultanate of Rum; Tarih; Trap; Turkey; Tuzak; Türkiye